2022
DOI: 10.18203/2349-3933.ijam20220436
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients diagnosed with supraventricular tachycardia: a descriptive study at a tertiary care hospital

Abstract: Background: Supraventricular tachycardia is a clinical syndrome characterized by a rapid tachycardia with an abrupt onset and termination. The objective of our study was to determine and assess the clinical profile, electrocardiographic and echocardiographic of patients diagnosed with supraventricular tachycardia.Methods: This cross-sectional study was conducted in the department of general medicine, Dr DY Patil medical college and hospital, Navi Mumbai from April 2020 till October 2021, in which we included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…In our study among the bradyarrythmia group 80% of children were found with complete heart block, 6.7% with highgrade AV block, and 13.3% with SN dysfunction. In study done by Beshoy Tamer Atta et al, A total of 70.5% of patients had sinus bradycardia, 13% had complete heart block (CHB), 10% had long QTc syndrome with sinus bradycardia, and 3.3% had first-and second-degree heart blocks, 18 . In our series 4 patients (13.3%) had large PDA while only 1(3.3%) presented with L-TGA with complete heat block.…”
Section: Discussionmentioning
confidence: 99%
“…In our study among the bradyarrythmia group 80% of children were found with complete heart block, 6.7% with highgrade AV block, and 13.3% with SN dysfunction. In study done by Beshoy Tamer Atta et al, A total of 70.5% of patients had sinus bradycardia, 13% had complete heart block (CHB), 10% had long QTc syndrome with sinus bradycardia, and 3.3% had first-and second-degree heart blocks, 18 . In our series 4 patients (13.3%) had large PDA while only 1(3.3%) presented with L-TGA with complete heat block.…”
Section: Discussionmentioning
confidence: 99%